2015
DOI: 10.1016/j.cell.2015.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity-Enhanced NMR Reveals Alterations in Protein Structure by Cellular Milieus

Abstract: Biological processes occur in complex environments containing a myriad of potential interactors. Unfortunately, limitations on the sensitivity of biophysical techniques normally restrict structural investigations to purified systems, at concentrations that are orders of magnitude above endogenous levels. Dynamic nuclear polarization (DNP) can dramatically enhance the sensitivity of NMR spectroscopy and enable structural studies in biologically complex environments. Here we applied DNP NMR to investigate the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
160
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(162 citation statements)
references
References 79 publications
2
160
0
Order By: Relevance
“…Short-range TEDOR spectra of these fibers revealed that whereas the majority of alanine sites had chemical shifts consistent with β-sheet or random-coil secondary structure (Fig. 4A), a quarter of the alanine sites had chemical shifts consistent with α-helical conformations, in line with previous observations of the M domain upon cryoprotection (47). This establishes that alanine takes on a variety of secondary structures in NM fibrils, consistent with its representation across the primary sequence of NM.…”
Section: Resultssupporting
confidence: 71%
“…Short-range TEDOR spectra of these fibers revealed that whereas the majority of alanine sites had chemical shifts consistent with β-sheet or random-coil secondary structure (Fig. 4A), a quarter of the alanine sites had chemical shifts consistent with α-helical conformations, in line with previous observations of the M domain upon cryoprotection (47). This establishes that alanine takes on a variety of secondary structures in NM fibrils, consistent with its representation across the primary sequence of NM.…”
Section: Resultssupporting
confidence: 71%
“…Dynamic nuclear polarization (DNP) methods are under continuing development as a means to achieve dramatic increases in sensitivity. A number of published studies have demonstrated the applicability to protein aggregate studies in particular [128132]. One interesting application is to study smaller amounts of labeled protein aggregates under dilute conditions, for instance in cellular extracts [132].…”
Section: Discussionmentioning
confidence: 99%
“…A number of published studies have demonstrated the applicability to protein aggregate studies in particular [128132]. One interesting application is to study smaller amounts of labeled protein aggregates under dilute conditions, for instance in cellular extracts [132]. Current DNP methods are typically reliant on cryogenic temperatures, which enhance the performance of dipolar-recoupling experiments, but also limit the ability to measure highly valuable dynamics data and often result in reductions in spectral resolution [82, 133].…”
Section: Discussionmentioning
confidence: 99%
“…However, except for a tiny percentage of cases (~ 1%), we do not know whether apparently disordered proteins can take on ordered states in vivo (Frederick et al, 2015) and the conditions for functional and structural experiments are unlikely to be known a priori for the vast majority. In the extreme, so-called fuzzy complexes have functional disordered regions that have been confirmed even when in their bound states (Tompa and Fuxreiter, 2008).…”
Section: Introductionmentioning
confidence: 99%